THE URGENCY OF SOCIOLOGY OF EDUCATION IN EDUCATIONAL INSTITUTIONS: LITERATURE REVIEW - Maharani, Okvi; Churrahman, Taufik; Nashrullah, Mochamad (PT. Antis International Publisher, 2024)
Education does not only involve mastering academic knowledge, but also involves forming a strong personality in students. Therefore, educational management that focuses on the sociology of education is very important to strengthen students' overall character. This research uses a literature study method to investigate the role of educational sociology in shaping student character through educational management. The aim of this research is to collect and display relevant reading material regarding the importance of educational sociology in educational management, using the literature review method. From the research results, it can be concluded that the implications of sociology are closely related to the field of education, as a scientific discipline that seeks to understand methods for managing the educational process in order to advance individual personality development. Sociology of education is in-depth and deals with various problems that arise in the educational context, especially in social interactions between students and their environment, teachers and peers. Apart from that, educational sociology also observes social phenomena that arise in the education system.